Plan de negocios para la ladrillera Arcillas Panorama (2010)
The clay Clay Panorama resumed its activities nine months ago, presenting in the moment problems with their productive activities as administrative, based on the information collected and with authorization of the owners, it is arranged to do in this work a business plan that will help managers take the necessary correctives so that the company work properly. The current problems presented by the organization are as follows, not have an organizational structure constituted in an organization chart, their diagrams are not set correctly with the requirement of production to meet the demand, the marketing area is not used to reach the target customer or business opportunity that may exist; as soon as to the products have several lines tiles, bluff brick, structural brick between others, although at the moment the product that is best marketed is the brick lighthouse, because the builders prefer this type of brick for their works, the brick lantern sells it to $ 420 pesos of first quality and of second quality at $ 350 pesos, really the prices are very standard with other of the region, differentiates them by the way in which they manufacture it and the clay used to make it. The bricklayers' market is small, but it does not comply with the amount of demand that exists at the moment in the market, is aimed at all strata, but mainly to the builders by the volume in the ones that they can acquire. The objective of this project is to investigate and solve the problems within the company so that it can improve its environment. internal and external, so that the business plan achieves goals and achievements at future. Financially the brick is not at its best, since the capacity of installation of the plant is more than 250,000 bricks and at the moment its system of production is in 150,000 bricks, why, it is due to several reasons between they do not have enough machinery for processing, they do not have the personnel trained enough to process the brick.